2020
DOI: 10.1111/jgs.16693
|View full text |Cite
|
Sign up to set email alerts
|

“Safety in Dementia”: Development of an Online Caregiver Tool for Firearm, Driving, and Home Safety

Abstract: to improve safety, offering both information to make decisions and practical suggestions for next steps. Additional testing of SiD is needed to evaluate its effects on behavior change and outcomes for both caregivers and people with dementia, as well as to identify the best methods for dissemination to at-risk populations. The development of tools like SiD offers the potential to support caregivers, the people they care for, and the community in promoting health while respecting independence and individual rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…SiD represents the first publicly available decision aid that addresses firearm access among people with dementia [ 6 ]. This trial demonstrated the feasibility of recruiting caregivers through MTurk and collecting efficacy outcome data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SiD represents the first publicly available decision aid that addresses firearm access among people with dementia [ 6 ]. This trial demonstrated the feasibility of recruiting caregivers through MTurk and collecting efficacy outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…We previously created the web-based Safety in Dementia (SiD) decision aid [ 6 , 7 ] to support care partners. SiD guides users through questions, such as those about preferences for in-home storage versus out-of-home storage or how a person with ADRD may react to no longer having access to firearms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that risk of suicide may be especially elevated in the period after an older adult receives a dementia or mild cognitive impairment diagnosis [43]. Talking with caregivers of patients with dementia about the risk of firearms remains rare [51], and experts suggest that conversations about firearms and dementia should parallel those about driving and dementia [52].…”
Section: Risk Factors For Firearm Suicidementioning
confidence: 99%
“…Data were collected as part of a parent project focused on engaging key stakeholders in developing “Safety in Dementia,” a decision support tool for ADRD caregivers 10 . For the parent study, we conducted one‐on‐one interviews with key informants from three key stakeholder groups: ADRD caregivers (professional, informal), medical professionals (geriatricians, neurologists), and firearm professionals (retailers, range employees, instructors).…”
Section: Methodsmentioning
confidence: 99%